EVALUATION OF A TERRACING MACHINE IN A SOIL OF SEMIARID REGION OF CEARÁ STATE - BULCÃO, J.P.; MELO, R.P.; DO NASCIMENTO, H.C.F.; DE FREITAS, C.R.; ALBIERO, D. (Revista Brasileira de Engenharia de Biossistemas, 2014)
The Soil preparation aims to provide conditions Ideal By establishing and Culture Development.Since the emergence of implements for soil preparation, there is concern in performing the improvement thereof.The greatest advances were to increase the ability of the work carried out by sets of machinesin order to improve preparation techniques itself.The terraceador is an agricultural implement very used to contour lines on slopes.Cutting angles of one terraceador discs interferes in the disc penetrating into the groundin height and width of the ridge which varies its shape.The objective was to evaluate the efficiency of different terraceador the angles of attack on the ground Ceará. The work was conducted at the Federal University of Ceará. The soil used for the test was a Red Yellow soil. One Valtra A950 tractor was used to pull the terraceador.Subsequently were performed 3 terracing operations in plots 50 feet for the angles 90 °, 100 ° and 110 °.Thereafter were the most basic measurement performed, base and height of the contour.Basic descriptive statistics were used to evaluate the data.Version 16 for data analysis - Microsoft Excel software and Minitab software was used.